A Kind of Chemistry - Laudan, Rachel (Petits Propos Culinaires, 1999)
The author explains that ’A kind of chemistry’ was the way the authors of The Gifts of Comus (1739) described the new cookery of the European courts, a cookery that had begun to take shape a century earlier with Pierre de la Varenne’s Le Cuisinier François (1651). This essay takes their metaphor at face value. It was indeed chemistry, a chemical cookery inspired by a radical group of chemical physicians who treated and advised the aristocracies of northern Europe. The author thanks Alan Davidson who accepted a preliminary sketch of this essay for ’A Mini-Symposium on New Publications’ PPC 53 (1996); 47-50, and the organizers and audiences of the Horning Lecture Series in History of Science at Oregon State University and Dibner Lectures in History of Science and Technology, Massachusetts Institute of Technology who bore with successive versions. The present version won the Sophie Coe Prize 1998.